The Effect of Demonstration Model to Social Studies Learning Outcomes - Nur Pebrianti, Eka; Suherman, Ade; Lili Dianah (Institut Pendidikan Indonesia, 2022)
This research is backgrounded by the low learning outcomes of students in social studies subjects because the learning outcomes in social studies subjects because the learning is still teacher-centred and the low number of teacher participating in training on the development of learning methods. One of the efforts in overcoming this is the need for innovative and effective learning methods, one of which is by using demonstration learning methods. This type of research uses a quantitative approach with a quasi-experimental method with a Nonequivalent Control Group Design design with a pretest-posttest design. The population of this study was class VII students of SMPN 2 Tarogong Kidul which amounted to 62 people.The sample in this study was VII-H as the experimental class and class VII I as the form of a test question sheet.The results showed that.1. There was no significant difference in the students initial abilities before the implementation of the demonstration method between the experimental class and the control class.2.There is a significant difference in the final abilities of students after the implementation of the demonstration method in social studies subjects.3.there is an increase in student learning outcomes after the implementation of the demonstration method in social studies subjects.The demonstration method is a waay of presenting learning by demonstrating or showing students a certain process, situation,or object according to the material being studied.The advantage of the demonstration method can encourage student learning motivation.As well as the demonstration method can liven up the lesson because students not only hear but also see the live events that are happening.This method will be easier for students can see directly,not just hear.